2020
DOI: 10.1021/acsaem.0c00737
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Electrolytes with Excellent Properties in a Wide Temperature Range

Abstract: A series of block copolymers (BCPs) with a polynorbornene backbone containing short poly(ethylene oxide) (PEO) side chains and rigid side chains were synthesized by tandem ring-opening metathesis polymerization (ROMP). The contents of PEO in the BCPs are regulated by the degrees of polymerization (DPs) of main chains. The crystallization of the PEO side chains is suppressed. Confirmed by small-angle X-ray scattering (SAXS) results, the BCPs doped with lithium salt and ionic liquid self-assemble into lamellar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…exhibited excellent σ (10 −4 S cm −1 at 30 °C and 6.41 × 10 −3 S cm −1 at 200 °C) based on block copolymers with a polynorbornene (PNBM) backbone containing short PEO side chains and rigid side chains by tandem ring‐opening metathesis polymerization with IL (1‐ethyl‐3‐methylimidazolium trifluoromethanesulfonate, EMImTFSI). [ 198 ] This high σ is attributed to a decrease in crystallinity and the formation of ion‐conducting channels at PEO domains for Li‐ion transport. In another investigation, Wang et al.…”
Section: Spes For Li‐based Secondary Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…exhibited excellent σ (10 −4 S cm −1 at 30 °C and 6.41 × 10 −3 S cm −1 at 200 °C) based on block copolymers with a polynorbornene (PNBM) backbone containing short PEO side chains and rigid side chains by tandem ring‐opening metathesis polymerization with IL (1‐ethyl‐3‐methylimidazolium trifluoromethanesulfonate, EMImTFSI). [ 198 ] This high σ is attributed to a decrease in crystallinity and the formation of ion‐conducting channels at PEO domains for Li‐ion transport. In another investigation, Wang et al.…”
Section: Spes For Li‐based Secondary Batteriesmentioning
confidence: 99%
“…Fan and co‐workers reported the high thermal stability of a BBCP membrane containing a PEO polynorbornene backbone with a T onset above 300 °C and suppression of crystallization of the PEO side chains as well as a highly stable liquid crystalline phase (over 200 °C), which further supports the high thermal stability of LiBs. [ 198 ] These studies showed that the T onset of SPEs is higher than the self‐heating temperature (120 °C) and the breakdown temperature of separators in conventional LiBs, which suggests that SPEs have superior thermal stability.…”
Section: Spes For Li‐based Secondary Batteriesmentioning
confidence: 99%
“…[ 7 ] Block copolymers consisting of an ion‐conducting block and a rigid block have been explored to prepare mechanically strong and conductive ionogels. However, most block copolymer ionogels possess insufficient ionic conductivity and low mechanical strength (e.g., room‐temperature ionic conductivity of 10 −4 S cm −1 and storage modulus well below MPa range) [ 8 ] to meet the needs for solid batteries, which limit the use of the ionogels. [ 9 ] Another approach for producing mechanically strong and highly conductive ionogels is using ionic polymers as an ionogel matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For the situation in which the conducting phase is in the majority, the morphology factor should always be 1. 14 However, the mechanical performance is usually quite poor when the conducting phase is in the majority because the content of the supporting domain is too low to maintain the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%